Análisis de la carta geomorfológica de la cuenca del Mapocho - Araya Vergara, José F. (Investigaciones Geográficas: Una mirada desde el sur, 1985)
The Mapocho basin (Central de Chile) is divided into two morphotectonic styles by the Mapocho fracture. ln the northern section, of the Santiago depression an intense monoclinal warping anda deep alveolar excavation evidence important uplift of the western border. ln the southern section, the asymetry is stronger than the former one and inverse, giving a fault angle depression. This fracturation of the depression’s bottom has affected both the conditions of sedimentation and the drainage patterns, causing antecedence phenomena and antagonistic effects between tectodynamics and external morphogenesis. Concerning present tectonics and seismicity, the presence both of different tectonic compartments and depositional landforms in the depression, is possibly more important than the faults themselves in the explanation of the distribution of seismic intensities. ln the northern section of the depression there is a characteristic combination between alluvial cones and "glacis" (bahadas). Moreover, marshy terraces correspond to bad drainage conditions. ln the southern section, in exchange, the central compartments are occupied by proximal cones and dista1 terraces. Slopes are presented as slope systems anda new classification supported on the structure and the external dynamics is used. At the same time, the concept of dissection balance allows relate slopes and talweg dynamics. Therefore, it can be known if the more important morphogenetic processes are present or ancient. So, the fluvial landforms at the depression’s bottom are inherited. In the present conditions it is unlikely the transport of coarse sediments from the high mountain toward the depression. Moreover, the torrentialand sheet wash morphologic systems are also inherited. Present through put of material from active slopes toward beds and depressions is possible only during heavy storms of rain y years.